Mapping Single-Cell Transcriptomes of Endometrium Reveals Potential Biomarkers in Endometrial Cancer - Xu G; Pan T; Li S; Guo J; Zhang Y; Xu Q; Chen R; Ma Y; Li Y (ImmunoTargets and Therapy, 2024)
Gang Xu,1,2,* Tao Pan,2,* Si Li,2,3,* Jing Guo,2 Ya Zhang,2 Qi Xu,2 Renwei Chen,4 Yanlin Ma,2 Yongsheng Li2,3 1College of Bioinformatics Science and Technology, Harbin Medical University, Harbin, 150081, China, Harbin, 150081, People’s Republic of China; 2Hainan Provincial Key Laboratory for Human Reproductive Medicine and Genetic Research, Reproductive Medical Center, National Center for International Research, The First Affiliated Hospital of Hainan Medical University, College of Biomedical Information and Engineering, Hainan Medical University, Haikou, Hainan, 571199, People’s Republic of China; 3School of Interdisciplinary Medicine and Engineering, Harbin Medical University, Harbin, Heilongjiang, 150081, People’s Republic of China; 4Hainan Women and Children’s Medical Center, Hainan Medical University, Haikou, Hainan, 571199, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongsheng Li; Yanlin Ma, Email liyongsheng@ems.hrbmu.edu.cn; mayanlinma@hotmail.comBackground: The heterogeneity and dynamic changes of endometrial cells have a significant impact on health as they determine the normal function of the endometrium during the menstrual cycle. Dysfunction of the endometrium can lead to the occurrence of various gynecological diseases. Therefore, deconvolution of immune microenvironment that drives transcriptional programs throughout the menstrual cycle is key to understand regulatory biology of endometrium.Methods: Herein, we comprehensively analyzed single-cell transcriptome of 59,397 cells across ten human endometrium samples and revealed the dynamic cellular heterogeneity throughout the menstrual cycle.Results: We identified two perivascular cell subtypes, four epithelial subtypes and four fibroblast cell types in endometrium. Moreover, we inferred the cell type-specific transcription factor (TF) activities and linked critical TFs to transcriptional output of diverse immune cell types, highlighting the importance of transcriptional regulation in endometrium. Dynamic interactions between various types of cells in endometrium contribute to a range of biological pathways regulating differentiation of secretory. Integration of the molecular biomarkers identified in endometrium and bulk transcriptome of 535 endometrial cancers (EC), we revealed five RNA-based molecular subtypes of EC with highly intratumoral heterogeneity and different clinical manifestations. Mechanism analysis uncovered clinically relevant pathways for pathogenesis of EC.Conclusion: In summary, our results revealed the dynamic immune microenvironment of endometrium and provided novel insights into future development of RNA-based treatments for endometriosis and endometrial carcinoma.Keywords: single-cell sequencing, cell–cell interaction, biological pathways, molecular subtypes, RNA biomarkers